2018
DOI: 10.1002/cam4.1406
|View full text |Cite
|
Sign up to set email alerts
|

Functional transcriptomic annotation and protein–protein interaction analysis identify EZH2 and UBE2C as key upregulated proteins in ovarian cancer

Abstract: Although early stage ovarian cancer is in most cases a curable disease, some patients relapse even with appropriate adjuvant treatment. Therefore, the identification of patient and tumor characteristics to better stratify risk and guide rational drug development is desirable. Using transcriptomic functional annotation followed by protein–protein interacting (PPI) network analyses, we identified functions that were upregulated and associated with detrimental outcome in patients with early stage ovarian cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Overexpression of MYOF has been associated with many cancers in humans, including breast cancer, lung cancer, and pancreatic cancer, and is shown to promote tumorigenesis, tumor cell motility, proliferation, migration, and metastasis [32][33][34]. Furthermore, other studies had reported up-regulation or down-regulation of TMEM156, ELOVL5, KIF23, AMPD3, CCNB1, CENPE, UBE2C, NXPE3, and PDE4DIP to be associated with numerous types of cancers in humans, such as breast cancer, ovarian cancer, non-small cell lung cancer, clear cell renal cell carcinoma, stomach cancer, colorectal cancer, esophageal cancer, pancreatic cancer, hepatocellular cancer, lung cancer, and prostate cancer [35][36][37][38][39][40][41][42][43][44][45]. Our results were consistent with the previous findings that indicated DEGs to possibly have great implication in tumor/cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MYOF has been associated with many cancers in humans, including breast cancer, lung cancer, and pancreatic cancer, and is shown to promote tumorigenesis, tumor cell motility, proliferation, migration, and metastasis [32][33][34]. Furthermore, other studies had reported up-regulation or down-regulation of TMEM156, ELOVL5, KIF23, AMPD3, CCNB1, CENPE, UBE2C, NXPE3, and PDE4DIP to be associated with numerous types of cancers in humans, such as breast cancer, ovarian cancer, non-small cell lung cancer, clear cell renal cell carcinoma, stomach cancer, colorectal cancer, esophageal cancer, pancreatic cancer, hepatocellular cancer, lung cancer, and prostate cancer [35][36][37][38][39][40][41][42][43][44][45]. Our results were consistent with the previous findings that indicated DEGs to possibly have great implication in tumor/cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, UBE2C, TOP2A, and KIAA0101 have node degrees exceeding 20. In recent years, it was found that UBE2C was lowly expressed in normal tissues while highly expressed in a variety of tumors such as lung cancer, [ 27 ] breast cancer, [ 28 ] ovarian cancer, [ 29 ] esophageal cancer, [ 30 ] and gastric cancer. [ 31 ] Overexpression of UBE2C positively correlates to poor prognosis in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism of UBE2C in HCC progression has not been elucidated. A previous study using transcriptomic functional annotation and protein–protein interacting network analyses demonstrated that the histone-lysine N-methyltransferase (EZH2) and UBE2C were identified as principal interacting proteins of druggable networks [18], implying that the EZH2–UBE2C interaction may be critical for cancer progression.…”
Section: Discussionmentioning
confidence: 99%